ETHICAL CONSIDERATIONS IN AI-DRIVEN DECISION MAKING: A FRAMEWORK FOR RESPONSIBLE AI IN BUSINESS - 1. Dr. Mayank Joshi, 2. Manoj Pahwa Sethi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study delves into the ethical considerations surrounding AI-based decision-making in business, proposing a framework for responsible AI. It addresses key concerns such as bias, transparency, accountability, and fairness. The research will assess the potential for AI systems to perpetuate biases, discriminate against specific groups, and lack clarity in their decision-making. It will also investigate methods to reduce these risks and ensure that AI is deployed ethically in business settings. This paper adds to the ongoing conversation about the ethical incorporation of AI in the financial sector, emphasizing the importance of integrating ethical principles into AI-driven financial decisions. As financial institutions seek to leverage AI’s capabilities, maintaining ethical standards becomes crucial, requiring strong governance and accountability structures. By closely analyzing these challenges, this paper provides valuable insights for the responsible integration of AI and ethics, paving the way for a sustainable and ethical technological future.